Increased creatinine kinase levels due to MDMA use without myoglobinuria and renal failure [MDMA kullanımı sonrası miyoglobinüri ve böbrek yetmezliǧi olmadan kreatin kinaz yüksekliǧi olan bir olgu sunumu] - (:unkn) unknown (Marmara University, 2012)
We report a 15-year-old boy admitted to the pediatric emergency unit with acute encephalopathy associated with an elevated serum creatine kinase (CK) level without myoglobinuria and renal failure, which was due to 3,4- Methylenedioxymethamphetamine (MDMA) toxicity and we emphasize that especially in adolescents with acute encephalopathy and an increased serum CK level, ecstasy abuse should be kept in mind as a differential diagnosis. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Adolescent; Delirium; Ecstasy; Increased CK level; Rhabdomyolysis